La podrelengua de Girondo - Raúl Antelo (Cuadernos LIRICO)
Girondo’s desire to fashion a language that would transcend all languages, beyond the reach of tradition and overcome all linguistic and historic nationalisms and ideologies, cannot simply be seen as an aesthetic gesture assumed by an elitist modernist. The crossing between a particularized literary idiolect and polyglottal trends could only be articulated by a strongly politicized pluridialect with a translinguistic as well as transcultural slant. That indissociable imbrication, from inside and/or outside, of the colonial and the national, or authority and subjection, opens to the fullness of an independent, self-authorizing voice.